Glitching trans* athletes: possibilities for research and practice in sports coaching. Issue 1 (2nd January 2022) - Linghede, Eva; Purdy, Laura; Barker-Ruchti, Natalie
ABSTRACT: The international discussion about policies regulating the inclusion of transgender athletes in elite sports is ongoing. . In this paper, we introduce the metaphor "glitch" to provide a novel way to embrace the possibilities of trans athletes in sport. To do this, we feature three Swedish cases of transgender athletes to consider: (1) What do "trans" and "trans athlete" mean from a glitch perspective? (2) What does this metaphor help us critique regarding sport's dual gender categorisation? and (3) How can glitch be a source to generate new ways to understand trans athletes? In thinking with glitch, we demonstrate that the "problem" of current trans discussions are not the bodies that transcend certain (gender) categories, but rather the dualistic categories themselves. Glitching athletes, trans or otherwise, help us turn what is taken for granted upside down, and in so doing, can help coaches, coach educators, and coaching researchers explore the possibilities of trans athletes in relation to their everyday sporting practices.